USING SHEEP FACIAL GRIMACE SCALE, INFRARED THERMOGRAPHY AND CORTISOL HORMONE TO MEASURE PAIN IN SHEEP INFECTED WITH MASTITIS DISEASE - Hussein, Nizar J.; Al-Naqshabendy, Assel A. (Science Journal of University of Zakho, 2024)
The purpose of this study was to apply sheep pain facial expression scales (SPFES) to sheep infected with mastitis, measuring peripheral temperatures and serum cortisol hormone. Twenty-three healthy ewes and 23 infected ewes with clinical mastitis were included in this research from January 2022 to April 2023. Images were taken from each ewe to detect facial grimace scales of ewes. Nasal, eye and ear temperatures were collected using infrared thermal imaging camera. Moreover, serum cortisol hormone was collected from the blood. It was found that there was a significant decrease (p<0.01) in nasal, eye and ear temperatures of infected ewes in comparison to healthy ewes. Additionally, cortisol hormone was found significantly (p<0.01) higher in infected ewes at day 1 and day 7 compared to non-infected animals. The changes in facial expressions for all the determined five regions were significantly (p<0.01) different than healthy ewes. The total pain score was significantly (p<0.05) higher on day 1 and day 7, compared to healthy ewes. It was concluded that sheep facial grimace scale was a useful and practical tool for measuring pain in sheep. In addition, cortisol from the serum and peripheral temperatures were found to be useful pain indicators.